Legal Protection of the Right to Patient Safety in Obstetric and Gynecological Medical Services - Fera Handayani; Abd. Rokhim (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
This article analyzes the concept of authority and the right to patient safety in obgyn medical services for legal protection for health human resources, patients, and the community. The purpose of the study is to analyze the legal protection of the concept of clinical authority and the right to patient safety in obgyn medical services in Indonesia, using normative juridical research with a legislative approach, conceptual approach, and comparison of secondary data in the form of regulations, Constitutional Court Decisions, books, legal magazines, articles and journals. The results and discussion state that the concept of health service authority is implemented through the determination of clinical authority by the head of the health facility, and Obgyn Doctors are authorized in medical services based on health service standards, medical service standards, and standard operating procedures. Protection of the right to patient safety in medical services is related to the function as a legal principle and fundamental norm of health services with equal rights and obligations between medical personnel and patients in a safer patient care system, including risk assessment, risk identification and management, reporting, incident analysis, learning from incidents and follow-up, and solutions to minimize risk and prevent injury.